Perinatal Outcome of Fetal Umbilical Vein Varix: A Multicenter Cohort Study [29P]. (May 2018) - Novoa Y Novoa, Victoria Arruga; Tonni, Gabriele; Prefumo, Federico; Ruano, Rodrigo
Abstract : INTRODUCTION: Umbilical vein varix (UVV) is a focal dilation of the fetal umbilical vein. Clinical significance is not clearly established but it has been associated with adverse outcomes. This study investigates the clinical outcomes of UVV diagnosed during pregnancy. METHODS: We performed a multicenter retrospective (USA, Chile, Italy and Brazil) study by reviewing 19 fetuses diagnosed with UVV between 2012 and 2017. We investigated gestational age at diagnosis and at delivery, UVV maximum diameter, fetal gender, associated anatomical anomalies, intrauterine growth restriction, fetal demise, type of delivery, birth weight, Apgar scores. RESULTS: UVV was diagnosed at 26.4+/- 4.4 weeks of gestation. Maximum diameter of the defect at diagnosis typically was 13.1+/- 5mm. The majority of fetuses were male (n=12, 63%). Growth restriction was diagnosed in 26% (n=5) of the fetuses. Seventeen (89%) infants survived. Fetal demise occurred in 2 (11%) patients; one was associated with structural anomalies, and the other fetus did not have any other associated anomaly. Vaginal delivery was performed in 10 (53%) patients; median weight at birth was 2870 g (270-4960 g). Median Apgar scores were 8 and 9 on 1st and 5th minutes consecutively (ranging from 0 to 10). Genetic and anatomical anomalies were present in 21% (n=4) of the fetuses and included: karyotype 47, XY+13, cleft lip and palate, cerebellar hypoplasia, aortic hypoplasia, cardiomegaly, Blake's pouch cyst, ambiguous genitalia, campomelic dysplasia with SOX9 mutation. CONCLUSION: UVV is a rare congenital condition that is usually associated with low frequency of other structural/genetic anomalies and with good prognosis. ACKNOWLEDGEMENTS: Waldo Sepulveda, Edward Araujo Junior, Mari Charisse Trinidad, and Heron Werner